THE DIVISION OF PARENTAL INHERITANCE BEFORE DEATH FROM THE PERSPECTIVE OF NIKLAS LUHMANN'S SOCIAL SYSTEM THEORY - Hidayat, Muhamad Ichsan; Jamaludin, Nurrun; Alimuddin, Khasan; Maulidya, Qotrunnada Sofy (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This research is motivated by the practice of distributing inheritance from parents to children before the parents die, which is widely practiced by the people of Kauman Kidul Village, Sidorejo District, Salatiga City. This culture shows a shift in values from the provisions of Islamic inheritance law and positive law which requires distribution to be carried out after the death of the testator. The purpose of this study is to determine the factors behind the occurrence of this practice and to understand its meaning as part of the social system of society. This research is a field study with a sociological approach and uses Niklas Luhmann's social system theory as an analytical tool. Data were collected through interviews with three local community leaders who were selected purposively and analyzed with the stages of data reduction, data presentation, and conclusions. The results of the study show that the distribution of assets is carried out through deliberation in the family and is often divided equally without distinguishing gender, although in some cases the eldest child or child who is not yet established gets a larger share. This practice is motivated by the desire to avoid family conflict and accelerate the child's ability and independence. From the perspective of social systems theory, this culture is a form of autopoietic family communication that is adaptive to social complexity, and reflects the function of the family in maintaining social harmony and stability.